Analisis Perancangan Tata Letak Ritel Abdidaya Mart dengan Metode Total Closeness Rating (TCR) - Bella Salsabila Cahyani; Eris Klarisa; Ivena Salcea; Rakha Hakiem Sinatrya; M. Makki Alfather (Jurnal Teknologi, 2023)
Appropriate strategies in retail management are very important to win the increasingly fierce retail industry competition, one of which is by implementing a retail business layout design. Abdidaya Mart is a retailer that provides goods for daily equipment. This study was conducted to analyze the route planning of product components to achieve the most efficient and economical flow between the movement of people, equipment, and materials by implementing a layout strategy. The analytical method used is the activity relationship chart (ARC) which focuses on analyzing the interrelationships between activities in the retail business and the total closeness rating (TCR) which focuses on the degree of proximity of each facility and department to the Abdidaya Mart retail business to determine the first priority in retail development. The ARC results show that several rooms absolutely must be close together, such as the cashier's room and the display room. The TCR value indicates the sequence of rooms that are prioritized in development, namely display space with a value of 198, a cashier with a value of 190, seats with a value of 109, warehouse with a value of 136, and toilets with a value of 37. Layout solution shows the arrangement of rooms described as the result of research This. The retail business layout design is useful for facilitating retail in managing efficient layout positions and can reduce the density of movement activities that occur in retail.